Prognostic value of tissue necrosis, hypoxia-related markers and correlation with HPV status in head and neck cancer patients treated with bio- or chemo-radiotherapy. Issue 1 (January 2018) - Ou, Dan; Garberis, Ingrid; Adam, Julien; Blanchard, Pierre; Nguyen, France; Levy, Antonin; Casiraghi, Odile; Gorphe, Philippe; Breuskin, Ingrid; Janot, François; Temam, Stephane; Scoazec, Jean-Yves; et al.
Abstract: Background and purpose: The aim of the present study was to investigate the role of three hypoxia-related biomarkers in patients with locally advanced head and neck squamous cell carcinoma (HNSCC) treated with concurrent chemoradiotherapy (3-weekly cisplatin) or bioradiotherapy (weekly cetuximab). Material and methods: In tumor tissue material from 100 patients with known HPV status, we evaluated the extent of tumor necrosis, the expression level of CA-IX and the microvascular density (MVD) measured as the density of CD34+ vascular structures. The correlations between biomarker expressions and clinicopathological characteristics and treatment outcomes were analyzed. Results: We found a significant correlation of MVD with UICC stage ( p = 0.02) and T classification ( p = 0.05), of CA-IX with UICC stage ( p = 0.03) and N classification ( p = 0.04) and a significant inverse correlation of MVD with CA-IX expression ( r = − 0.22, p = 0.03). Multivariate analysis showed that low MVD combined with high CA IX-expression was a significant independent prognostic factor for worse loco-regional control (HR = 2.6, 95%CI 1.1–5.0, p = 0.02) in the whole population but not in the p16+ subgroup. Patients treated with CRT had a better LRC than those with BRT independent of MVD or CA-IX expression. Conclusions: The combination of MVD and CA-IX expression might give additional prognostic information in HNSCC patients with known HPV status.